Factor Analysis of Service Quality in University Libraries in Sri Lanka – An Application of Servqual Model - Velnampy, T.; Sivesan, S. (My University, 2013)
This research paper seeks to advance the application of SERVQUAL tool developed by Parasuraman et.al (1985) for measuring services quality. In Sri Lanka, realizing the necessity of complying with customer perception of high quality service, have begun to search for alternative ways to satisfy their customer on the basis of service quality. This study, therefore, examines the factors determining the service quality of university libraries. . Primary and secondary data were used to conduct the study. Sophisticated statistical model as “Exploratory Factor Analysis” (EFA) has been used. The study reveals that four factors extract from the analysis that together accounted 50.317% of the total variance. These factors were categorized as convenient opening hours, current information, collection comprehensiveness and convenient access to collection.
Keywords: Service quality; SERVQUAL model; convenient; current information; comprehensiveness; convenient access